Exploring contributing factors on holistic well-being among Malaysian youth - Mohamed, Nor Aini; Alby, Jeffrey Lawrence D'Silva; Abu Samah, Asnarulkhadi; Mohamed Shaffril, Hayrol Azril; Dahalan, Dzuhailmi (Human Resource Management Academic Research Society, 2018)
The Global Youth Wellbeing index includes 35 indicators across seven domains that is gender equality, economic opportunity, education, health, safety and security, citizen participation and information and communication technology. Youth signifies the developmental phase where critical decisions are taken on the key life transitions including; continuing education, entering work, adopting healthy lifestyles, starting a family and participating in society. The purpose of this paper is to explore the factors that contribute to holistic wellbeing among Malaysian youth. The Nominal Group Technique was used to address the question ‘What influence the well-being of youth? The group participants were nine youth ages 19 -29 years. Item generation was followed by discussion for clarification and operationalisation. The results indicated that self-recognition, love, quality time, entertainment, health, vacation, education, ICT, spirituality, wealth, peace, interpersonal relationship and infrastructure, influence the well-being of youth. This study highlighted some important findings that could be used as guidelines in conducting further research on the well-being of youth in Malaysia. Interventions implemented on improving youth well-being should cover on individual, family, learning institutions as well as community level.